Reactivity of the Hypothalamic-Pituitary Gonadal System after 10 Minutes of Clinical Death - Karabaev Aminjon Gadaevich; Kim Diana Vladislavna (Research Parks Publishing LLC, 2022)
When modeling a 10-minute clinical death, changes in the reproductive system were studied in white mature male rats with a weight of 180-220 g. Clinical death was modeled according to the method of V.G.Korpachev (1982). The reproductive state in intact and experimental rats was studied using morphological, morphometric, histochemical, cytophotometric biochemical research methods. At the same time, the reproductive system in index rats is in a state of moderate functioning to highlight the synthesis and secretion of testosterone. During the period of clinical death, there is an increase in the functional activity of d-basophil cells of the adenohypophysis, the content of the Lethinating hormone provided an increase in testosterone secretion.